PENGGUNAAN MOBILE HEALTH DALAM USAHA MONITORING HIPERTENSI[THE UTILIZATION OF MOBILE HEALTH IN MONITORING HYPERTENSION] - Saras Anindya Nurhafid; Tuti Afriyani (Universitas Pelita Harapan, 2018)
Hypertension is a health problem that is still widely encountered in Indonesia. A common problem is the lack of monitoring of health status by hypertensive patients. With the advancement of information technology, has designed mobile health information system known as mHealth which can be integrated with Electronic Health Record (EHR) in health service to improve hypertension monitoring. The author uses literature review non sistematic study writing method. Implementation of mHealth has benefits both for mHealth users and for health teams, especially community nurses who can improve the quality of health services. Therefore, the authors recommend the use of mHealth in health services in Indonesia. Keywords: Electronic Health Record, hypertension, mHealth